Pengaruh Kualitas Produk, Kepuasan Konsumen, Promosi, dan Brand Image Terhadap Minat Beli Mahasiswa pada Air Minum Le Minerale - Bella Risma; Fadzil Hanafi Asnora; Syukron Arjuna (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
Drinking water is a basic human need that must be available to everyone because it is essential for survival. Due to the high demand for drinking water, many producers see an opportunity to run businesses in this field, as this product is always needed anywhere and anytime. This study aims to determine the influence of product quality, customer satisfaction, promotion, and brand image on the purchasing interest of students in Le Minerale bottled water (Case Study at Universitas Labuhanbatu). This research uses a descriptive quantitative method. The population of this study consists of all students at Universitas Labuhanbatu who have purchased and consumed Le Minerale at least three times, although the exact number of the population is unknown. The sample used consists of 91 respondents. Each student tends to Students choose bottled water because there are many brand and type options, it is easy to find, the prices vary, and it offers good benefits.